Drug Oversupply in Nursing Homes - An Empirical Evaluation of Administrative Data - Magdalena A. Stroka (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
A widely discussed shortcoming of long-term care in nursing homes for elderly is the inappropriate or suboptimal drug utilization, in particular the utilization of psychotropic drugs. This paper estimates the effect of institutionalization on the drug intake of frail elderly using administrative data from the largest sickness fund in Germany. Difference-in-differences propensity score matching techniques are used to compare drug prescriptions of frail elderly who entered a nursing home with those who remained in the out-patient care system. The findings suggest that nursing home inhabitants receive more doses of antipsychotics, antidepressants and analgesics. The potential oversupply goes along with estimated drug costs of about exteuro 87 million per year. – – Unter Rückgriff auf die Routinedaten Deutschlands größter Krankenkasse analysiert die vorliegende Studie die Unterschiede der in einem Jahr verschriebenen Dosen verschiedener Arzneistoffklassen im ambulanten und stationären Pflegebereich. Erstmalig in der Literatur werden dabei im Rahmen der Untersuchung von Verschreibungsunterschieden potenziell inadäquate Medikationen für ältere Menschen betrachtet. Die Ergebnisse des Difference-in-difference Propensity Score Matchings zeigen, dass im stationären Pflegebereich mehr Antipsychotika, Antidepressiva und Schmerzmittel verordnet werden als in der ambulanten Pflege. Diese potenzielle Überversorgung geht mit jährlichen Medikamentenkosten in Höhe von etwa exteuro 87 Millionen einher.
Keywords: I10; 330; medication errors; patient safety; expenditures; drug over- and undersupply; medical costs